Unemployment Benefits as a Substitute for a Conservative Central Banker - Tella, Rafael Di; MacCulloch, Robert (The Review of Economics and Statistics, 2004)
In the many years since their introduction, positive theories of inflation have rarely been tested. This paper documents a negative relationship between inflation and the welfare state (proxied by the parameters of the unemployment benefit program) that is to be expected in such theories. Because unemployment benefits make the monetary authority less concerned about the plight of the unemployed, building a welfare state has a similar effect to appointing a conservative central banker. The relationship holds in a panel of 20 OECD countries over the period 1961–1992, a region where Romer finds no evidence of commitment problems. It holds controlling for country and time fixed effects, country specific time trends, other covariates, and using a decadal panel. Interpreted as causal, the estimated effect is economically large: a 1-standard deviation decrease in benefit duration is predicted to add 1.4 percentage points onto inflation, or 31% of the standard deviation in inflation.